First laboratory X‐ray diffraction contrast tomography for grain mapping of polycrystals. (25th October 2013) - King, A.; Reischig, P.; Adrien, J.; Ludwig, W.
<x xml:space="preserve">Abstract</x> The first results of three‐dimensional grain mapping using a laboratory tomograph equipped with a microfocus W target X‐ray tube source, operated at 90 kV and 350 µA, are presented. Adapted algorithms exploit the polychromatic radiation spectrum and the projection magnification arising from the cone‐beam geometry. The first map of grain shapes and crystallographic orientations from a titanium sample containing 42 grains is presented and its validity confirmed by a phase contrast reconstruction of the grain boundaries. Perspectives are given for the further development of the technique to accommodate samples with more grains or with greater intragranular orientation spread.